Pulsed Laser Photo-Crosslinking of Gelatin Methacryloyl Hydrogels for the Controlled Delivery of Chlorpromazine to Combat Antimicrobial Resistance - Tatiana Tozar; Simona Nistorescu; Mihai Boni; Gratiela Gradisteanu Pircalabioru; Irina Negut; Angela Staicu (MDPI AG, 2022)
Hydrogels are ideal candidates for the sustained local administration of antimicrobial drugs because they have customizable physicochemical properties that allow drug release kinetics to be controlled and potentially address the issue of systemic side effects. Consequently, the purpose of this study was to use 266 nm-pulsed laser beams to photo-crosslink gelatin methacryloyl hydrogels using Irgacure 2959 as a photo-initiator to reduce the curing time and to have an online method to monitor the process, such as laser-induced fluorescence. Additionally, irradiated chlorpromazine was loaded into the hydrogels to obtain a drug delivery system with antimicrobial activity. These hydrogels were investigated by UV-Vis and FTIR absorption spectroscopy, scanning electron microscopy, and laser-induced fluorescence spectroscopy and their structural and morphological characteristics, swelling behavior, and drug release profile were obtained. As a result the morphology, swelling behavior, and drug release profile were influenced by both the energy of the laser beam and the exposure time. The optimal hydrogel was obtained after 1 min of laser irradiation for Irgacure 2959 at 0.05% w/v concentration and gelatin methacryloyl at 10% w/v concentration. The hydrogels loaded with irradiated chlorpromazine show significant antimicrobial activity against Staphylococcus aureus and MRSA bacteria and a non-cytotoxic effect against L929 fibroblast cell lines.